Effect of Nursing Care Strategy on Functional Outcomes among Patients after First Time Stroke - Marwa M. Ali; Rasha F. Mohamed; Amina A. Mahmoud (Evidence-Based Nursing Research)
Context: Strokes are life-changing events not merely affect a person physically but also emotionally as it may result in physical disabilities, which lead to functional disabilities as difficulties carrying out daily activities as working, walking, talking, eating, bathing, with loss of energy in addition to depressive status as a result of functional disabilities. Daily nursing care strategies are essential to stroke management. Since, it can overcome spasticity and hemiplegia through sustained stretching by various positioning, repetitive performance of a specific movement, and teaching patient to use and adapt the affected limb during functional activities.